Projeto para criação do Centro de Pesquisa e Documentação de História Oral e Ciências Sociais (Beira, Moçambique) - Dunduro, Silva Armando (2009)
The main goal of this dissertation is to propose the creation of a Center of Research and Documentation of Oral History and Social Sciences in the city of Beira, Mozambique. It is intended that the Center will be encharged of promoting projects related to the constitution of a set of collections with historical and documental contents, that will be able to contribute to the development of academic research and the valorization of Mozambican history and culture. The Center will have the oral history as its main methodological research tool. The collections, that will be formed based upon different projects, will be the result of interviews, recorded with actors who come from different social strata, all of them directly envolved in important events of Mozanbican recent history. These interviews should be available at the Center, altogether with other kinds of sources, gathered and organized with the objective of constituting a reference center related to the Mozanbique’s contemporary history. All the Center activities will be supported by projects of teams’ qualification. In this sense, the Center will have to deal with two basic fields: the research, production, preservation and diffusion of sources to the national contemporary history; and the didactic-pedagogical support to the different levels of learnship process.